ANTIMICROBIAL EFFECT AND INSILICO ADMET PREDICTION OF SANTALUM ALBUM L. - KUSHAL K. HIRE; D. A. DHALE (International Journal of Pharma and Bio Sciences, 2012)
Santalum album L. is known as East Indian Sandalwood Plant and is well known for its Heartwood. The Sandalwood heartwood contains two major photochemical i.e. Santalol and Santyl acetate. For this study different fractions of Heartwood and leaves are extracting in Soxhlet assembly with organic solvents as well as pure Heartwood oil was extracted by steam distillation method in Clavenger assembly. Fractions and Oil were screened against few human pathogens by disc diffusion method. Methanol fraction and Oil resulted in high potential against Escherichia coli, Staphylococcus aureus and S.typhi. In silico prediction of Santalol and Santayl acetate using PRE-ADMET, shows 100% Human intestinal absorption and plasma protein binding, Positive against carcinogenic cell lines, Positive CNS-Barrier test, which affirms them as potent antibacterial and anticancerus lead compound.